Pengaruh Ukuran Perusahaan dan Umur Perusahaan terhadap Manajemen Laba dengan CSR sebagai Variabel Intervening - Fitri Yeni; Putri Intan Permata Sari; Nelvia Nelvia (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine how much influence firm size and firm age have on earnings management by disclosing corporate social responsibility as an intervening variable. The method of data collection is by observing the financial statements of manufacturing companies published on the Indonesia Stock Exchange in the 2015-2019 period. The analysis method used is path analysis and sample collection techniques is purposive sampling, with a sample 0f 33 companies. The data used in this study are the company's annual financial statements obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The results of this study found that firm size has no effect on corporate social responsibility as an intervening variable. There is no influence between firm age on corporate social responsibility as an intervening variable. Firm size affects earnings management. There is no influence between firm age on earnings management. There is an influence between corporate social responsibility on earnings management. Corporate social responsibility cannot mediate firm size on earnings management. Corporate social responsibility can mediate the firm age on earnings management.